2018
DOI: 10.1089/jpm.2017.0157
|View full text |Cite
|
Sign up to set email alerts
|

Improved Pain Control in Terminally Ill Cancer Patients by Introducing Low-Dose Oral Methadone in Addition to Ongoing Opioid Treatment

Abstract: Addition of low-dose oral methadone to regular high-dose opioid treatment in cancer patients with complex pain close to death improves pain control, but also increases the risk for sedation and delirium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 20 publications
4
19
1
1
Order By: Relevance
“…Methadone was highlighted as an important component of the palliative toolbox because it was easy to handle and had rapid onset, often within a few hours. The notion of methadone treatment being successful in 50-90% of selected patients is mainly in line with previous reports of the effects of low-dose methadone add-on therapy [15,18,35,36].…”
Section: Indications For Methadone and Refractory Pain Situationssupporting
confidence: 87%
See 3 more Smart Citations
“…Methadone was highlighted as an important component of the palliative toolbox because it was easy to handle and had rapid onset, often within a few hours. The notion of methadone treatment being successful in 50-90% of selected patients is mainly in line with previous reports of the effects of low-dose methadone add-on therapy [15,18,35,36].…”
Section: Indications For Methadone and Refractory Pain Situationssupporting
confidence: 87%
“…There is emerging evidence that low-dose methadone as an add-on twice daily to already existing high-dose opioid treatment increases the pain-relieving effect in complex pain [14][15][16][17][18]. This is also the general opinion in the current study.…”
Section: Recommendations For Future Researchsupporting
confidence: 51%
See 2 more Smart Citations
“…96 Retrospective studies have also reported that low-dose methadone may improve pain control when used as a coanalgesic in patients with cancerrelated pain that were receiving a different, regularly scheduled opioid analgesic. 97,98 There is evidence suggesting that high doses of methadone (120 mg and above) may lead to QTc prolongation and torsades de pointes, which may lead to sudden cardiac death. [99][100][101] A study conducted in patients with cancer suggests that QT interval changes exist commonly at baseline and are not changed with the addition of methadone.…”
Section: Methadonementioning
confidence: 99%